2022
DOI: 10.1021/acscatal.2c03476
|View full text |Cite
|
Sign up to set email alerts
|

Neighboring Cationic Vacancy Assisted Adsorption Optimization on Single-Atom Sites for Improved Oxygen Evolution

Abstract: Single-atom catalysts with particular electronic and geometric microenvironments provide an atomic-scale perspective for research into the mechanism of catalysis. Designing the neighboring geometry of single-atom catalysts can tailor the adsorption configuration of reaction intermediates and enhance their activity in catalytic reactions. In this work, we proposed a neighboring cationic vacancy strategy in single-atom Ru catalysts to adjust the adsorption configuration of reaction intermediates for improved oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Furthermore, the selected rectangular regions show the change in the line intensity profile, where atomic positions with significantly reduced intensity indicates the presence of Ni v (Figure 1h). [ 17,18 ] The nanosheets are successfully exfoliated from ≈25 nm to ≈5 nm (Figure 1i,j), as further confirmed by atomic force microscopy (AFM). [ 19 ] The generation of Ni NPs is also verified by the Ni 2p X‐ray photoelectron spectroscopy (XPS) spectra with the appearance of Ni(0) (Figure 1k).…”
Section: Resultsmentioning
confidence: 73%
“…Furthermore, the selected rectangular regions show the change in the line intensity profile, where atomic positions with significantly reduced intensity indicates the presence of Ni v (Figure 1h). [ 17,18 ] The nanosheets are successfully exfoliated from ≈25 nm to ≈5 nm (Figure 1i,j), as further confirmed by atomic force microscopy (AFM). [ 19 ] The generation of Ni NPs is also verified by the Ni 2p X‐ray photoelectron spectroscopy (XPS) spectra with the appearance of Ni(0) (Figure 1k).…”
Section: Resultsmentioning
confidence: 73%
“…introduced a strategy of utilizing cationic vacancies in the support of SAC to enhance the OER performance. [ 177 ] The OER performance of the catalyst Ru 1 ‐V Co ‐Co(OH) 2 , which has neighboring Co 2+ vacancies on the Co(OH) 2 , was found to be superior compared to a catalyst without Co 2+ vacancies (Ru 1 ‐Co(OH) 2 ). The mass activity of Ru 1 ‐V Co ‐Co(OH) 2 is 4.7 times higher than that of Ru 1 ‐Co(OH) 2 .…”
Section: Energy Conversion Applicationsmentioning
confidence: 99%
“…The adjustment of the coordination environment can not only change the kind of coordination atoms but also change the vacancies around the metal center. Bao and coauthors reported that a Ru single-atom catalyst with neighboring Co 2+ vacancies based on Co­(OH) 2 shows 4.73 times activity in OER performance compared to that of a catalyst without Co 2+ vacancies . The result of DFT calculations manifested that with Co 2+ vacancies *OOH intermediates can form a hydrogen bond with the neighboring O atom, which tunes the absorption configuration of *OOH and lowers the energy barrier of OER.…”
Section: Intrinsic Activity Of Single Sitementioning
confidence: 99%